Cities and rural transformation: A spatial analysis of rural livelihoods in Ghana - Diao, Xinshen; Magalhaes, Eduardo; Silver, Jed (Elsevier, 2019)
Recent growth in many African countries has been accompanied by rapid urbanization, which could have major impacts on rural livelihoods. This paper examines patterns of rural livelihoods and poverty in Ghana based on the proximity of rural areas to cities of different sizes. The paper finds that many rural households in the areas close to cities have shifted their primary employment from agriculture to nonagriculture, especially in the more urbanized South. This trend strengthens over time. This appears to take place in contrast to the traditional model of rural livelihood diversification, with some family members working in agriculture and some in nonagriculture. Although cities have created market demand for agriculture, proximity to cities does not seem to influence agricultural intensification in terms of modern input use, possibly due to agricultural markets being relatively integrated in Ghana. Proximity to cities has implications for rural households being less poor and becoming middle class even after controlling for being a nonfarm household in rural areas.